First report on cold-sprayed AlCoCrFeNi high-entropy alloy and its isothermal oxidation. Issue 5 (13th March 2019) - Anupam, Ameey; Kumar, S.; Chavan, Naveen M.; Murty, Budaraju Srinivasa; Kottada, Ravi Sankar
Abstract: Abstract : Cold-sprayed high-entropy alloy (HEA) coatings have been generated for the first time. Mechanically alloyed (MA) AlCoCrFeNi powder was chosen as feedstock, owing to the extensive literature on this alloy. Coatings were synthesized under various gas temperature and pressure conditions. Isothermal oxidation was conducted at 1100 °C for 25 h on the coating cold-sprayed at 400 °C and 10 bar on a Ni-base superalloy substrate. The as-sprayed coating retained the MA phases and formed a protective alumina layer upon oxidation. An interdiffusion zone at the interface and unanticipated Mo diffusion from the superalloy substrate into the coating were observed after oxidation. A comprehensive characterization at the coating–substrate interface suggests that diffusion in HEAs is not sluggish. The factors governing the coating's oxidation are elucidated, and a plausible oxidation mechanism is discussed. These studies are aimed at developing oxidation-resistant HEA coatings for potential applications at high operating temperatures.